2016
DOI: 10.3164/jcbn.16-49
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the adequate dosage of rebamipide, a gastric mucoprotective drug, to prevent low-dose aspirin-induced gastrointestinal mucosal injury

Abstract: Small intestinal mucosal injury caused by low-dose aspirin is a common cause of obscure gastrointestinal bleeding. We aimed to investigate the protective effects and optimal dose of rebamipide for low-dose aspirin-induced gastrointestinal mucosal injury. In this prospective randomized trial, 45 healthy volunteers (aged 20–65 years) were included and divided into three groups. The groups received enteric-coated aspirin 100 mg (low-dose aspirin) plus omeprazole 10 mg (Group A: proton pump inhibitor group), low-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 43 publications
0
27
1
Order By: Relevance
“…[90][91][92] Small RCTs of healthy subjects supported that rebamipide had the potential to reduce NSAID-induced small intestinal injury. 29,[31][32][33]37 Kurokawa et al 35 performed a multicenter study involving 61 patients who had received more than 3 months of low dose aspirin and/or NSAID to take rebamipide (100 mg 3 times daily for 4 weeks) or placebo and found that rebamipide had the protective effect for NSAIDs-induced enteropathy by reducing the number of small intestinal ulcers and erosions as evaluated by capsule endoscopy. Another small multicenter study by Watanabe et al 36 also found that 8 weeks of highdose rebamipide (300 mg 3 times daily) significantly decreased the number of mucosal breaks and improved intestinal dam-age severity.…”
Section: Rebamipidementioning
confidence: 99%
See 1 more Smart Citation
“…[90][91][92] Small RCTs of healthy subjects supported that rebamipide had the potential to reduce NSAID-induced small intestinal injury. 29,[31][32][33]37 Kurokawa et al 35 performed a multicenter study involving 61 patients who had received more than 3 months of low dose aspirin and/or NSAID to take rebamipide (100 mg 3 times daily for 4 weeks) or placebo and found that rebamipide had the protective effect for NSAIDs-induced enteropathy by reducing the number of small intestinal ulcers and erosions as evaluated by capsule endoscopy. Another small multicenter study by Watanabe et al 36 also found that 8 weeks of highdose rebamipide (300 mg 3 times daily) significantly decreased the number of mucosal breaks and improved intestinal dam-age severity.…”
Section: Rebamipidementioning
confidence: 99%
“…Another small multicenter study by Watanabe et al 36 also found that 8 weeks of highdose rebamipide (300 mg 3 times daily) significantly decreased the number of mucosal breaks and improved intestinal dam-age severity. However, Ota et al 37 reported that standard-dose rebamipide (100 mg 3 times daily) was sufficient for preventing mucosal injury of the small intestine induced by low-dose aspirin, indicating that high-dose rebamipide (300 mg 3 times daily) may not be necessary. A systematic review and meta-analysis 34 including 15 RCTs and 965 individuals, provided consistent results that rebamipide is effective and safe for defending against NSAID-induced lower GI injuries.…”
Section: Rebamipidementioning
confidence: 99%
“…This implied that changes in Hct levels may not be sensitive enough to detect minimal chronic blood loss if the patients have compensatorily high levels of red blood cell production. This was supported by Ota et al 23 who showed that even using direct methods for assessing small bowel lesions with fecal occult blood tests and capsule endoscopies may not be sufficiently sensitive to detect early small bowel injury.…”
Section: Discussionmentioning
confidence: 87%
“…In addition to preventing gastric ulcers, rebamipide may prevent small bowel injury in patients taking NSAIDS or aspirin . Therefore, we examined blood Hct levels to assess occult blood loss during the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation